Organizing for Independence: Secessionist Protest, Organizational Change, and the Referendum Crisis in Catalonia - Hans Jonas Gunzelmann (Amsterdam University Press, 2024)
Independence protests are on the rise across Europe, as Spain, the UK, and other states have faced severe secessionist challenges. The largest wave of these protests swept Catalonia and reached its peak in 2017 when the push for a binding referendum led to an unprecedented secessionist crisis. Organizing for Independence explores the question of how the referendum crisis as a threat and opportunity transformed secessionist protest and its organizational basis. Combining protest event data, qualitative interviews, and network analyses, Hans Jonas Gunzelmann shows how organizational change took place inside, outside, and between formal organizations, and was driven by activists' symbolic constructions of transformative events. The book goes beyond simplistic accounts of secessionist protest by providing a dynamic perspective on strategic interactions between protesters and their opponents and allies. These insights are particularly timely as independence movements all over the world look with great interest at what happened in Catalonia.
Additional information: Funding note: "The publication of this book is made possible thanks to the Leibniz Open Access Publishing Fund for Monographs, the Center for Civil Society Research at the WZB Berlin Social Science Center, and the Fritz Thyssen Stiftung."
Keywords: 300; repression; Catalan; revolutionary; separatist; organisations